Relationship between School Principals' Toxic Leadership Behaviors and Teachers' Organizational Silence - Demirtas, Zulfu; Kucuk, Ozkan (Dergipark Akad, 2019)
The perception level of high school and secondary school teachers concerning toxic leadership behaviors of school administrators and their organizational silence behaviors and the effect of toxic leadership behaviors of school administrators on teachers' organizational silence was examined in this study. The study was carried out through the relational screening model. The Toxic Leadership and Organizational Silence scales were conducted on 411 teachers working in ten high schools and eight secondary schools in the province of Elazig and which were selected through the cluster sampling method. A regression analysis along with the average and standard deviation values were used in analyzing the study data. Perception levels of teachers concerning the toxic leadership behaviors of their school administrators were observed to be at low level; perception levels concerning their own organizational silence behaviors were observed to be at moderate level. Teacher perceptions concerning toxic leadership behaviors of their school administrators are significant predictors of their organizational silence.
Keywords: leader; toxic leader; organizational silence